Conditional Intravesical Recurrence-Free Survival Rate After Radical Nephroureterectomy With Bladder Cuff Excision for Upper Tract Urothelial Carcinoma - Chung, Jae Hoon; Song, Wan; Kang, Minyong; Jeon, Hwang Gyun; Jeong, Byong Chang; Seo, Seong IL; Jeon, Seong Soo; Lee, Hyun Moo; Sung, Hyun Hwan (Frontiers in Oncology, 2021)
Background: To evaluate the conditional intravesical recurrence (IVR) free(IVRF) survival rate in patients with upper tract urothelial carcinoma (UTUC) who had no history of bladder cancer and no concomitant bladder cancer. Hence, we aimed to analyze a relatively large number of patients with UTUC who underwent radical nephroureterectomy with bladder cuff excision (RNUx). Methods: We retrospectively analyzed the data of 1,095 patients with UTUC who underwent RNUx. Their baseline characteristics, bladder tumor history, and UTUC features were analyzed to evaluate oncological outcomes. To determine the factors affecting IVR, surgical modality, use of preoperative ureteroscopy, TNM stage, and pathological outcomes were evaluated. Multivariable Cox regression analyses were performed to evaluate the factors affecting IVR. Conditional IVR-free survival rate was analyzed using Kaplan–Meier curves. Results: Among the 1,095 patients, 462 patients developed IVR, and the mean time to the development of IVR was 13.08 ± 0.84 months after RNUx. A total of 30.74% of patients with IVR and 15.32% of those without IVR had a history of bladder cancer (p < 0.001). Multivariable analysis showed that a history of bladder cancer, multifocal tumors, use of preoperative ureteroscopy, extravesical bladder cuffing method, lymph node involvement, positive surgical margins, and use of adjuvant chemotherapy were determined to be risk factors for IVR. The conditional IVRF rate was 74.0% at 12 months after RNUx, 87.1% at 24 months after RNUx, 93.6% at 36 months after RNUx, and 97.3% at 60 months after RNUx. The median IVRF survival period was 133.00 months for all patients. In patients with IVRF at 24 months after RNUx, only ureteroscopy was an independent risk factor for IVR (HR 1.945, p = 0.040). In patients with IVRF at ≥36 months, there was no significant factor affecting IVR. Conclusions: Active IVR assessment is required until 36 months after RNUx. In addition, patient education and regular screening tests, such as urine analysis and cytology, are required for patients with IVRF for ≥36 months.